أثر المناخ التنظيمي علي سلوك المواطنة التنظيمية لدى موظفي مؤسسة صيدال – عنابة، الجزائر - كبير, عمر; بن علي, عبد الرزاق (University of Eloued جامعة الوادي, 2019)
هدفت الدراسة إلى تحديد طبيعة العلاقة السببية بين الاقتصاد الموازي والموارد العامة في الاقتصاد الجزائري خلال الفترة ) 1990 - 2018 ،) وذلك عن طريق تحليل بيانات سنوية باستخدام منهجية غرانجر لاختبار العلاقة السببية وفق ثلاث مراحل وهي اختبار جذر الوحدة باستخدام ديكي فولر الموسع، واختبار توازن طويل الأجل بين بيانات السلسلتين باستخدام جوهانسن، اختبار غرانجر للسببية في المدى القصير. دلت نتائج الاختبارات على عدم وجود تكامل مشترك بين حجم الاقتصاد الموازي والموارد العامة، كما أنه لا توجد علاقة توازنية في الأجل الطويل بين متغيرتي الدراسة، وأن العلاقة السببية كانت باتجاه حجم الاقتصاد الموازي إلى الموارد العامة في المدى القصير Abstract: This study aims to determine the impact of the organizational climate on the organizational citizenship behavior of employees of the SAIDAL company - Annaba. To achieve this, the study adopted the descriptive analytical approach. A questionnaire was designed to collect initial data for a sample of 79 employees. To analyze the data, the arithmetic mean, standard deviation and simple linear regression test were used, based on spss 22.0. The results of the study revealed that the level of organizational citizenship behavior among employees was high, and a strong positive trend towards the organizational climate prevailing in the institution under study. The results of the study also showed that the prevailing organizational climate and its dimensions have an impact on organizational citizenship behavior among employees. The study recommends "SAIDAL company - Annaba" officials to further improve the regulatory environment, broaden the base of participation in decision-making, and instill a spirit of teamwork to facilitate the transfer of expertise and the strengthening of relationships between employees.
The effect of the organizational climate on the organizational citizenship behavior of employees SIDAL Company - Annaba, Algeria
مقال - مجلة رؤى اقتصادية
Keywords: مناخ تنظيمي، سلوك المواطنة التنظيمية، نمط القيادة، أنظمة اتصالات، صيدال. الترميز الاقتصادي ) JEL :) M12 ، O1; organizational climate, organizational citizenship behavior, leadership style, communication systems, SAIDAL Jel Classification Codes: M12 ،O15